Haji Ahmad Baik and the emergence of Islamic scholar in Bujang Valley, Kedah / Syazliyati Ibrahim ... [et al.] - Ibrahim, Syazliyati; Wan Omar, Maznah; Mohammed, Syakirah (2018)
This research studies a Muslim religious scholar name Haji Ahmad bin Haji Yahya from the state of Kedah. One would wonder how Haji Ahmad gained the nickname Haji Ahmad Baik which stands for Ahmad the good. The methodology adopted in this study was through the adoption of the oral history method and was found deemed appropriate for this type of study. Nevertheless the study also draws a picture of how a respectable character such as Haji Ahmad Baik was brought and become a respectable character in Bujang Valley. He contributed to the teaching of Islam in the Bujang Valley by conducting classes from one mosque to another. However, due to the popularity of Madrasah Sa’adatut Darain which was initiated by Haji Ahmad Baik. A similar madrasah was built in the next hamlet, Kampung Bendang Dalam, with Haji Ahmad Baik as the teacher. The idea of sekolah pondok flourished during Haji Ahmad Baik’s time and his kindness and his strong faith in God were justly rewarded.